Спосіб завантаження сипких матеріалів в клапанні мішки - Оришака, О. В.; Кравцов, А. О.; Оришака, В. О.; Артюхов, А. М.; Oryshaka, O.; Kravtsov, A.; Oryshaka, V.; Artiukhov, A.; Оришака, О. В.; Кравцов, А. А.; Оришака, В. А.; Артюхов, А. Н. (Український інститут промислової власності, 2008)
Корисна модель відноситься до фасувально-пакувальних процесів і може бути використана в агропромисловості, будівельній, хімічній та інших галузях господарства, а також на підприємствах, які здійснюють фасування сипких матеріалів. A method of loading of bulk materials in valve bags includes the stage of free flight of bulk material during its motion, the stage, at which it is compacted, which is carried out during its motion in to the reduced channel in the direction motion, and the stage, at which it is partially aerated, which is performed by a jet of compressed air, the direction of action of which coincides with the direction of motion of bulk material.
Method of loading of bulk materials in valve bags